Elective Fetal Reduction in Dichorionic Diamniotic Twin Pregnancies on Parental Request: A Single-Centre Experience. Issue 10 (October 2021) - Kaul, Anita; Prasad, Smriti; Anand, Keerthana; Arora, Saloni; Sharma, Akshatha
Abstract : (Abstracted from Fetal Diagn Ther 2021;48:272–278) The incidence of multiple gestations is increasing because of increases in both maternal age and infertility treatments. Multifetal pregnancy reduction (MFPR) is a safe procedure that has not been associated with a substantial risk of miscarriage and has been associated with better pregnancy outcomes in terms of prematurity and neonatal birth weight.